Aproveitamento de resíduos da cadeia sucroalcooleira para geração de energia - Ilário, Carla Valério (Universidade Federal de São Carlos, 2020)
Many residues are generated in the industrial processes of the sugar and alcohol plants, sugarcane bagasse is one of them. Often, without proper treatment, they end up being just another waste with added value wasted and released into the environment. However, when used correctly in industrial processes, they guarantee energy efficiency - generating energy from the burning of bagasse - and economical, avoiding the commercialization of energy for a production unit. The objective of this work is to identify which strategy is used by most sugar and alcohol plants today, as limitations for increasing the supply of surplus electricity and directed to overcome them. To achieve the objectives of the work, it was used as a methodology the case study of two São Paulo plants. It was evidenced that the studied plants employ the strategy of self-sufficiency in the generation of energy and only one negotiates the surplus for external sales. This is mainly due to the costs associated with the commercialization of energy, which are high, both for the purchase and the sale of surplus energy and, also, for the overcoming of regulations and bureaucracies for this trade. To overcome the obstacles and encourage the plants to produce energy for commercialization and not only for their self-sufficiency, it would be necessary government incentives, such as lower negotiation rates for buying and selling or greater rewards for those who use and produce clean energy. For today and for the future, new sources of reinforced renewable energy being studied and developed, many of them are linked to the sugar and alcohol sector, in addition to bagasse, we have filter cake and vinasse. This scenario favors the country, which today has an energy matrix centered on water potentials, which are finite and seasonal.
Use of residues from the sugar-alcohol chain for power generation
Keywords: resíduos; bagaço; cadeia sucroalcooleira; geração de energia; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA